TANGGAPAN WISATAWAN TENTANG ATRAKSI GAJAH DI PLG MINAS KABUPATEN SIAK - Rilla Safitri; Andi M Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Response is perception picture who live in our awareness after make apperception to things or object. Response can be permission, expostulation, question and opinion. Response divided to become 3 faction, that is pursuant or according to sense observed, includes response auditory, visual, taste fan etc. according to occurrence ncludes memory fantasy and mind. While according environmental there is object and words etc. This research uses descriptive quantitative method to know tourist response . The sample in this study were 135 respondents, taken using accidental sampling. While data collection techniques in this study using observation, questioner, and interviews. By using a Likert scale as a measure to determine the length of the short interval. With indicator on visual, memory, fantasy,mind and words. (agus sujanto 2009). From the results of research conducted in the field of research on the tourist response about elephant attraction in PLG Minas District Siak , with the theory of tourist response is divided into three indicator: visual, memory, fantasy, mind and words, the results field in the can that is on the tourist respon of elephant attraction in PLG Minas District Siak and the result of reseach included in the agree category.Keywords : response, attraction,visual, memory, fantasy, mind and words.